Social capital: potential for action research of an emerging paradigm - Fernández Fernández, José Manuel (Cuadernos de Trabajo Social, 2012)
The use of the term «social capital» has increased exponentially during the recent decades to the point at which its relevant meanings risk being ruined for social analysis and intervention. In this paper, a critical evaluation is made of the applications of this idea by social scientists that, from many different theoretical perspectives, have contributed to its current development. It is argued that it has not attained the status of a unified paradigm. As an example of its potential for social analysis and intervention, the model worked out by Woolcock for the development of poor communities has been chosen.
Keywords: community; development; inequality; structure; capital; networks; resources; relations; link comunidad; desarrollo; desigualdad; estructura; redes; recursos; relaciones; vínculo